2016
DOI: 10.1002/14651858.cd010351.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Participation in environmental enhancement and conservation activities for health and well-being in adults: a review of quantitative and qualitative evidence

Abstract: Participation in environmental enhancement and conservation activities for health and well-being in adults: a review of quantitative and qualitative evidence (Review)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
69
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(77 citation statements)
references
References 109 publications
5
69
0
3
Order By: Relevance
“…Quality was appraised using the Wallace criteria to determine the appropriateness of the method and quality of reporting (Wallace, Croucher, Quilgars, & Baldwin, ), see Table . This has been used in previous qualitative reviews (Greaves, Poltawski, Garside, & Briscoe, ; Husk, Lovell, Cooper, Stahl‐Timmins, & Garside, ; Moore et al., ), and covers research question, theoretical perspective, study design, context, sampling, data collection, data analysis, reflexivity, generalisability and ethics. Studies were assigned ‘yes’, ‘no’ or ‘can't tell’ for desirable and essential criteria which generated an overall score of ‘good’, ‘moderate’ or ‘poor’ (Husk et al., ).…”
Section: Methodsmentioning
confidence: 99%
“…Quality was appraised using the Wallace criteria to determine the appropriateness of the method and quality of reporting (Wallace, Croucher, Quilgars, & Baldwin, ), see Table . This has been used in previous qualitative reviews (Greaves, Poltawski, Garside, & Briscoe, ; Husk, Lovell, Cooper, Stahl‐Timmins, & Garside, ; Moore et al., ), and covers research question, theoretical perspective, study design, context, sampling, data collection, data analysis, reflexivity, generalisability and ethics. Studies were assigned ‘yes’, ‘no’ or ‘can't tell’ for desirable and essential criteria which generated an overall score of ‘good’, ‘moderate’ or ‘poor’ (Husk et al., ).…”
Section: Methodsmentioning
confidence: 99%
“…Contribution to the synthesis was evaluated by re‐examining the qualitative synthesis (eg, the documentation of the results of each of the individual stages of the qualitative synthesis) to understand which papers substantively contributed data, concepts and understanding to identification and development of the overarching themes and sub‐themes. The synthesis of qualitative studies as reported in our Cochrane Review was used . Once each paper's contribution to the overarching and sub‐themes was identified in the synthesis, we determined which studies were (1) fundamental and necessary to the specific overarching and/or sub‐theme (we term these key studies ) and (2) which papers merely added confirmatory validity or data richness (we term these additional studies ).…”
Section: Methodsmentioning
confidence: 99%
“…These 22 databases included the following: MEDLINE (Ovid), Embase (Ovid) and The Cochrane Library (Wiley interface) as well as Social Policy and Practice (Ovid), IBSS (Pro Quest) and ASSIA (Pro Quest), CAB Abstracts and Greenfile. The full list of bibliographic databases searched, and our MEDLINE search strategy, is included in the published Cochrane Review . The Trial Search Co‐Ordinator of The Cochrane Public Health Group checked and approved our searches.…”
Section: Developing the Cochrane Study Identification Protocol And Tamentioning
confidence: 99%
See 1 more Smart Citation
“…Such interventions should be tailored, not only to an individual's desires and goals towards socially engagement, but to how social isolation relates to their personal musculoskeletal pain experiences and beliefs. Whilst such strategies may be costly to both health and social care services (Husk et al, 2016;Mossabir et al, 2015), this may be offset through reduced health and service care burden in accident and emergency admissions, formal and informal carer costs and reduced primary and secondary care utilisations (Husk et al, 2016;Landeiro et al, 2016;Lim et al, 2006;Mossabir et al, 2015). Through this, biopsychosocial features of an individual's disease can be sufficiently addressed for sustainable improvements in symptom management and social engagement.…”
Section: Recommendationsmentioning
confidence: 99%